Authorship in Croatian copyright legislation from 1846 to 2007 (Libellarium: journal for research in the field of information and related sciences, 2015)
The aim of this paper is to investigate and present concepts of the author and his/her copyright work in copyright legislation that entered into force in Croatia from 1846 to 2007. 17 legal documents (acts, corrigenda, amendments) were investigated using the content analysis method. The analysis of the results gives an insight into various cultural and sociological dimensions of authorship in the given time-frame. Special attention was paid to definitions of the author and his/her copyright work, examples of copyright works and exceptions related to the duration of copyright for different kinds of copyright works. As there had been no systematic overview of such legal documents in the available literature, they were briefly described in the first part of the paper, highlighting the important articles that stress the role of authors and their copyright work. In the analysis and summary we provide a systematic overview of the main concepts, with a special review of copyright laws in relation to new technologies and artistic forms: it is their relationship that testifies to the complexity of the term 'copyright work'. The paper shows that the basic perception of the author, his/her copyright works and their relations in the analysed copyright legislation has not changed significantly during this period of time. All legal documents refer to the examples of copyright work, and in 1957 a definition of copyright work was included, according to which copyright work is every spiritual (later referred to as intellectual) creation. The concept of the author is strongly linked with the concept of author's copyright work. Various examples of copyright works allow us to see the difference between works that are permanent (e.g. literary works, music works, art works) and works that are yet to be protected by copyright thanks to the development of technology and new features of artistic expression (e.g. photography, movies, computer programs). The process of getting copyright is reflected in articles that regulate the duration of copyright.
Keywords: author; copyright work; copyright legislation; copyright act; Croatia